MicroRNA390-Directed TAS3 Cleavage Leads to the Production of tasiRNA-ARF3/4 During Somatic Embryogenesis in Dimocarpus longan Lour - Lin, Yuling; Lin, Lixia; Lai, Ruilian; Liu, Weihua; Chen, Yukun; Zhang, Zihao; XuHan, Xu; Lai, Zhongxiong (Frontiers in Plant Science, 2015)
Trans-acting short-interfering RNAs (tasiRNAs) originate from TAS3 families through microRNA (miRNA) 390-guided cleavage of primary transcripts and target auxin response factors (ARF3/-4), which are involved in the normal development of lateral roots and flowers in plants. However, their roles in embryo development are still unclear. Here, the pathway miR390-TAS3-ARF3/-4 was identified systematically for the first time during somatic embryo development in Dimocarpus longan. We identified the miR390 primary transcript and promoter. The promoter contained cis-acting elements responsive to stimuli such as light, salicylic acid, anaerobic induction, fungal elicitor, circadian control and heat stress. The longan TAS3 transcript, containing two miR390-binding sites, was isolated; the miR390- guided cleavage site located near the 3' end of the TAS3 transcript was verified. Eight TAS3-tasiRNAs with the 21-nucleotide phase were found among longan small RNA data, further confirming that miR390-directed TAS3 cleavage leads to the production of tasiRNA in longan. Among them, TAS3_5'D5+ and 5'D6+ tasiRNAs were highly abundant, and verified to target ARF3 and -4, implying that miR390-guided TAS3 cleavage with 21-nucleotide phase leading to the production of tasiRNA-ARF is conserved in plants. Pri-miR390 was highly expressed in friable-embryogenic callus (EC), and less expressed in incomplete compact pro-embryogenic cultures,while miR390 showed its lowest expression in EC and highest expression in torpedo-shaped embryo. DlTAS3 and DlARF4 both exhibited their lowest expressions in EC, and reached their peaks in the globular embryos stage, which were mainly inversely proportional to the expression of miR390, especially at the GE to CE stages. While DlARF3 showed little variation from the EC to torpedo-shaped embryos stages, and exhibited its lowest expression in the cotyledonary embryos stage. There was a general lack of correlation between the expressions of DlARF3 and miR390. In addition, miR390, DlTAS3, DlARF3, and -4 were up-regulated by 2,4-D in a concentration-dependent manner. They were also preferentially expressed in roots, pulp, and seeds of ‘Sijimi’ longan, implying their extended roles in the development of longan roots and fruit. This study provided insights into a possible role of miR390-tasiRNAs-ARF in plant somatic embryo development.